1989
DOI: 10.1103/physrevb.39.12903
|View full text |Cite
|
Sign up to set email alerts
|

Sequential precursors in dissociative chemisorption:O2on Pt(111)

Abstract: A physisorbed state for 02 on Pt(111) has been identified by XPS spectroscopy and demonstrated to be an intrinsic precursor to molecular chemisorption. Combined with the prior demonstration that the molecularly chemisorbed species is a precursor to dissociation, we propose a model of sequential precursors to describe dissociation.Precursor species have often been invoked to describe the kinetics of adsorption, desorption, and dissociative chemisorption of gases on surfaces. This concept, dating from the semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(96 citation statements)
references
References 15 publications
2
93
1
Order By: Relevance
“…Compared to the oxygen interactions with metal-oxide surfaces, theoretical studies on metallic surfaces (2PBs) have been more extensively reported as summarized in [101]. In order to examine the oxygen reduction reaction at the 2PBs in SOFC applications, Pt [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] and Ag [116,[148][149][150][151][152][153][154][155][156][157][158] cathode materials will be discussed. It is well known that different surface morphologies, subsurface elements and surface charges induce d-band shifting of the metal electrodes and change O 2 dissociation barriers in different surface orientations [130].…”
Section: Oxygen Reduction On Metallic Surfaces and Tpbsmentioning
confidence: 99%
“…Compared to the oxygen interactions with metal-oxide surfaces, theoretical studies on metallic surfaces (2PBs) have been more extensively reported as summarized in [101]. In order to examine the oxygen reduction reaction at the 2PBs in SOFC applications, Pt [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] and Ag [116,[148][149][150][151][152][153][154][155][156][157][158] cathode materials will be discussed. It is well known that different surface morphologies, subsurface elements and surface charges induce d-band shifting of the metal electrodes and change O 2 dissociation barriers in different surface orientations [130].…”
Section: Oxygen Reduction On Metallic Surfaces and Tpbsmentioning
confidence: 99%
“…Various phases of atomic and molecular oxygen have been proposed to interpret electron energy loss spectroscopy (EELS) [31][32][33], thermal desorption spectroscopy (TDS) [32][33][34][35][36], near-edge X-ray-absorption spectroscopy [37][38][39], and photoemission spectroscopy [31,34] . This corresponds to the current bridge state, which is considered to form a covalent bond from each O to an on-top site of Pt.…”
Section: Comparison With Experimental and Other Studiesmentioning
confidence: 99%
“…Adsorbed molecular oxygen is found at 150 K; at higher temperatures dissociation takes place. 7 Previous spectroscopic studies identified three distinct chemisorbed states of oxygen on the Pt͑111͒ surface. Two of them are adsorbed molecular species, the superoxo-like (O 2 Ϫ ) state is formed at bridge sites with an intramolecular bond order of 1.5 and a vibrational frequency of 870 cm…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental point of view, there is evidence for the dissociative adsorption of O 2 at the platinum-ultrahigh vacuum ͑UHV͒ interface at room temperature, 7 but there is no evidence for the direct cleavage of the O-O bond at the electrochemical interfaces.…”
mentioning
confidence: 99%